Diagnóstico de gestión productiva del sector cárnico vacuno minorista del cantón Bolívar basado en el estudio de factores críticos de éxito. - Cruz Zambrano, Jennifer Valeria (2018)
The objective of this work was to diagnose the productive management of the beef bovine retail sector of Bolívar canton, based on the study of critical success factors. In the research development of the study object, methods such as: deductive, inductive and descriptive were used, and the survey technique was applied, which was based on the five critical factors of success: processes, capacity, inventories, strength of work and quality; it was assigned to a sample of 282 retail producers, once the results were obtained, the data was tabulated in the SPSS program and the current situation was known; Obtaining as results that the producers lack knowledge about the productive management, do not have adequate facilities, farmers do not keep records of production on their farms, under knowledge about proper feeding for cattle, among other problems. A proposal was made for an improvement plan that contributes to the improvement of production management in small producers in the Bolívar canton area.